Analisis Pengaruh Kepuasan Kerja terhadap Loyalitas Karyawan di Rumah Sakit Siaga Al Munawwarah Samarinda - Trifosa Trifosa; M Ardan; Herni Johan (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2025)
Loyalty and job satisfaction have a significant influence on improving performance so that efforts to improve performance are carried out through increasing job satisfaction. Information shows that the number of employees who stop working at the hospital has increased and decreased by >10% each year. The purpose of this study was to analyze the effect of job satisfaction on employee loyalty at the Siaga Al Munawwarah Hospital Samarinda. This study used a cross-sectional design method with a population of 144 employees and a sample of 103 employees selected through purposive sampling. Data collection was carried out using a questionnaire, then analyzed using simple linear regression. The results of the analysis showed that job satisfaction had a positive and significant influence on employee loyalty, indicated by the p-value (0.000 <0.05). This finding emphasizes the importance of job satisfaction in improving employee loyalty and performance, especially in the health sector.